The Fifth International Conference on Altitude/Hypoxia Training at the Beijing Sport University. Does adaptation to hypoxia enhance sea-level elite performance? - Hopkins, W. (Sportscience, 2015)
Review on the 5th International Conference on Altitude/Hypoxia Training an der Beijing Sport University: This biennial conference consisted of lectures by seven invited speakers trans-lated on-the-fly for the Chinese audience. Peter Wagner explained the physio-logical basis of limitations to endurance performance that altitude training has to overcome. Will Hopkins explained how to make inferences about the effects of altitude. Yannis Pitsiladis spoke of the as yet unrealized promise of ge-nomics technologies for personalizing altitude training. Rob Aughey focused on the need to get the training itself right. Martin Burtscher provided evidence of the health benefits of adapting to hypoxia, especially the intermittent variety. Chris Gore presented a strong case for altitude enhancing performance via an increase in hemoglobin mass, offset by low iron status, illness, and negative energy balance. Carsten Lundby asserted that altitude training had no benefit for top endurance athletes with high hemoglobin mass, but a small temporary benefit for some such athletes seems more likely.